PENGARUH PENGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR IPAS KELAS 4 SDN 15 SITIUNG - Burhan, Maldin Ahmad; Hasibuan, Rusdi Indra; Melina, Aria (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This type of research uses a quasi-experimental design research type with a Pre – test-Post- test Non-Equivqlent Graoups Design. The population in this study were all students in grade 4 of SDN 15 Sitiung, while the sample used was students in grade 4 A as a control class totaling 20 students and class 4 B as an experimental class totaling 17 students of SDN 15 Sitiung. In this study, the data were taken using purposive sampling technique, data collection technique using Pre – test-Post- test sheet test, then analyzed using normality test, homogeneity test, and hypothesis test through SPSS 25 at the 0.05 level. The results of the influence of the use of the Wordwall-assisted CTL model on student learning outcomes in the content of IPAS chapter 5 type A B and chapter 6 topic A class 4 SDN 15 Sitiung were declared valid. Based on the results of the analysis of test data from the hypothesis test, homogeneity and Paired sample T test with a significance level of 0.05 showed the sig. (2-tailed) is smaller than a or in the equation 0.000 <0.05, then Ho is rejected and Ha is accepted. Based on the results of the analysis of the test data, it can be concluded that the Wordwall-assisted CTL model has a significant influence on student learning outcomes in the content of IPAS class 4 SDN 15 Sitiung.